Penyimpangan Undang-Undang Nomor 13 Tahun 2022 dengan Prinsip Meaningfull Participation - Moh. Ishomuddin (Jurnal Hukum Lex Generalis, 2024)
Public participation in the formulation of legislation is a manifestation of people’s sovereignty, as stipulated in Article 1 paragraph (2) of the 1945 Constitution and reinforced by Constitutional Court Decision No. 91/PUU-XVIII/2020 on meaningful participation. This normative juridical study analyzes Law No. 13 of 2022 and finds that the rights of the public to be heard, considered, and given explanations have not been fully implemented. This may weaken legal legitimacy and trigger social conflicts. Therefore, the mechanism for public participation must be strengthened to ensure the quality of democracy in the legislative process in Indonesia.